EFEKTIVITAS ASAM RETINOIK PADA PENYEMBUHAN LUKA PERFORASI BARU MEMBRAN TIMPANI HEWAN COBA MARMOT - Daniel Widjaja (Bahasa Indonesia, 2022)
Introduction: Tympanic membrane (TM) perforation is common in our practice, it may be due to infection or trauma. Retinoic acid (RA) has been studied for its effect on wound healing, it can stimulate angiogenesis and increase the rate of re-epithelialization in wounded skin. The purpose of this study is to determine the effectiveness and the rate of healing of RA in wound closure of acute TM perforations in Guinea pigs Methods: This is a randomized control trial animal experimental study, twenty Guinea pigs (40 TM) were used. Randomization to determine group for intervention and control was done using the toss coin method. A small perforation using spinal needle G 20 was done. RA was introduced in the intervention group while in the control group, TM was allowed to heal spontaneously. All TM were examined on day 3, 7, 10 and 14. Recording of perforation was done with endoscopic system. Measurement of the TM as well as the perforation was done by using a graphic program (AutoCAD R14). Results: TM healed completely on day 14 in the intervention group and the control group was 52.9 % and 47.1% respectively with p =0.492. The rate of healing on day 3,7 and 10 in the intervention group and the control group was 0.15 & 0.08; 0.38 & 0.69; 0.29 & 0.58 respectively with p= 0.01; 0.003 and 0.001. Conclusion: Tympanic membrane with RA treated group showed a significant rate of healing on day 3,7 and 10. However, RA have no significant effect on closure of acute traumatic perforations after day 14